PERAN BAHASA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PROSES DEMOKRASI PADA PEMILU 2024 - Mahyudi, Arni (SINERGI : Jurnal Riset Ilmiah, 2024)
This study aims to explore the role of language in increasing community participation in the democratic process, specifically in the 2024 General Election in Amawang Kiri Village. A qualitative approach with a case study design was used to understand the social phenomenon in the village, where language plays a significant role in electoral communication. Data was collected through in-depth interviews with the Election Committee (PPS), community leaders, and villagers involved in the election, as well as observations of election socialization activities. The findings indicate that using language that is easy to understand and more inclusive enhances the community's understanding of the election process and encourages more active participation. This research provides recommendations on communication strategies that use local language and more accessible approaches for rural communities to improve the quality of participation in the 2024 General Election.